The Implementation of the Task-Based Learning Model to Improve Business Correspondence Learning at SMK PAB 2 Helvetia - Ali, Nurbaiti; Fadilah, Nina; Habib, Muhammad (Indonesian Research Journal on Education, 2025)
This study explores the implementation of the Task-Based Learning (TBL) model to improve students' writing skills in business correspondence at SMK PAB 2 Helvetia. The research follows a Classroom Action Research (CAR) methodology, comprising two cycles with a focus on the four stages: planning, action, observation, and reflection. The primary objective was to enhance the students' ability to write effective business correspondence, such as business emails and letters. In Cycle 1, only 38% of students met the Minimum Completeness Criteria (MCC) of achieving a score of 85 or higher, indicating the need for adjustments in task design. After incorporating changes in Cycle 2, such as additional feedback and revised task complexity, 90% of the students achieved the MCC, demonstrating significant improvement. The study highlights the effectiveness of TBL in engaging students with real-world tasks, leading to enhanced writing skills. This research contributes to the pedagogical understanding of integrating TBL in vocational education, particularly for improving business communication skills in the digital age.